The intellectual structure and thematic evolution of skin cancer research in the Middle East - Ahmad Assiri (Medicine, 2026)
Background: Skin cancer research in the Middle East has grown substantially over recent decades, yet its intellectual and collaborative landscape remains underexplored. This study aimed to map the evolution, thematic structure, and collaboration patterns of regional skin cancer research (1946–2025), benchmarking these trends against global trajectories to identify emerging conceptual domains and research priorities. Methods: Six comprehensive Scopus-derived datasets – categorized by duration, document type, and collaboration scope – were analyzed using Bibliometrix (R), VOSviewer, and CiteSpace. Analyses included productivity trends, choropleth mapping, citation impact, comparative metrics, co-authorship networks, keyword co-occurrence, thematic evolution, and cluster detection. Callon centrality–density model was applied to map thematic maturity, and CiteSpace was used to identify emerging clusters (2021–2025). All procedures followed the BIBLIO-checklist. Results: A total of 179,158 initial records were retrieved from Scopus. After applying progressive filters, 6 datasets were constructed: dataset 1 (n = 7932), dataset 2 (n = 5640), dataset 3 (n = 5329), dataset 4 (n = 3869), dataset 5 (n = 2107), and dataset 6 (n = 1260). Regional research exhibited a 7.38% annual growth rate but lagged in international co-authorship (2.74% vs 33.31% globally). Thematic analyses showed a shift from clinical dermatology toward AI-driven diagnostics, dermoscopy, and melanoma. Turkey, Iran, and Egypt accounted for over 70% of regional output. Visualizations revealed fragmented intra-regional networks but strong external ties with the U.S. and Europe. CiteSpace clustering highlighted melanoma cell lines and absorption spectroscopy as recent focal areas. Conclusion: Middle Eastern skin cancer research is gradually adopting computational and translational approaches. However, collaboration gaps and limited citation impact underscore the need to strengthen regional networks, promote open access, and invest in integrative, technology-driven research platforms.